STRATEGI PENGEMBAGAN DESTINASI WISATA PANTAI (SEBUAH ANALISIS TEORITIS) - Desrika Talib; Sri Sunarti (Program Studi S1 Pariwisata, Universitas Muhammadiyah Gorontalo, 2020)
Indonesia as an archipelagic country has a very big opportunity to develop coastal tourism. This type of tourism is increasingly favored by the community both among children, youth and adolescents as well as the elderly. One of sectors being developed in the world today is coastal tourism. Advances in technology, easy access and transportation have a positive impact in developing coastal tourism. The research method is a literature review with descriptive qualitative research type. The results showed that several things that must be considered in the development of coastal tourism destinations are; 1. Amenity (tourist facilities, both main and supporting facilities). 2. Accessibility (access roads and transportation systems to reach wista destination locations). 3. Ancillary Service (an institution or a government or private institution capable of providing services for tourists). Theoretical studies related to developer strategy for developing coastal tourism destinations are salient to always be developed and updated in realizing the sustainability of a tourist destination.